Análise independente de Gauge e redução Hamiltoniana completa da gravitação induzida em duas dimensões - Devecchi, F. P [UNESP] (1992)
We analyze in this work two dimensional induced gravity both pure and coupled to matter fields along two approaches; quantum and classical gauge independent analysis for the pure model and a classical study via reduced phase space for both models, introducing gauge fixing constraints which depend explicitly on time